2000
DOI: 10.1097/00004647-200001000-00023
|View full text |Cite
|
Sign up to set email alerts
|

N-Type Ca2+ Channels in Cultured Rat Sphenopalatine Ganglion Neurons: An Immunohistochemical and Electrophysiological Study

Abstract: Summary:Results from pharmacological studies have sug gested that presynaptic N-type Ca 2 + channels play an important role in regulating neuronal Ca 2 + influx and transmitter nitric oxide (NO) release in isolated cerebral arteries. However. the presence of N-type Ca 2 + channels in cerebral perivascular nerves has not been directly demonstrated. As a major source of cerebral perivascular NOergic innervation is the sphenopalatine ganglion (SPG), adult rat SPGs were cultured and examined by whole-cell patch-cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…Under our experimental conditions, the total number of isolated neurons per animal was 1213 ± 134 (SEM; n=3). This yield is greater than that reported in a previous study (< 100 neurons/rat) employing SPG [15]. In the first set of experiments, immunofluorescence assays were employed to determine the neurochemical phenotype of the acutely dissociated SPG neurons.…”
Section: Nih Public Accessmentioning
confidence: 90%
See 1 more Smart Citation
“…Under our experimental conditions, the total number of isolated neurons per animal was 1213 ± 134 (SEM; n=3). This yield is greater than that reported in a previous study (< 100 neurons/rat) employing SPG [15]. In the first set of experiments, immunofluorescence assays were employed to determine the neurochemical phenotype of the acutely dissociated SPG neurons.…”
Section: Nih Public Accessmentioning
confidence: 90%
“…The yield of neurons obtained was approximately 10-fold higher than previously reported [15]. Also, the neurons were not kept in culture for long periods (< 24 hr) in order to avoid growth of processes that would affect clamp control in our experiments.…”
mentioning
confidence: 87%
“…Freshly dissected SCGs from animals were placed in cold Hibernate A (Invitrogen, Carlsbad, CA, USA) solution (Liu et al, 2000). After being cut into smaller pieces, the ganglia were transferred to Mg 2 + /Ca 2 + -free Hanks'-balanced salt solution containing papain (2 U/ml; Sigma-Aldrich, St Louis, MO, USA), collagenase D (1.2 mg/ml; Roche Diagnostics, Indianapolis, IN, USA), and dispase (4.8 mg/ml; Invitrogen), and were incubated for 50 mins at 371C.…”
Section: Superior Cervical Ganglion Cell Culturementioning
confidence: 99%
“…Previous studies have also shown that PPG parasympathetic neurons are predominantly cholinergic by nature, however the presence of other neurotransmitter markers including tyrosine hydroxylase or nitric oxide synthase has been additionally noted [7]. Besides, major neurotransmitter PPG neurons also express various neuropeptide receptors [8] as well as a bulk of neuroactive peptides acting as neuromodulators and/or co-transmitters [9][10][11]. Recently, the presence of novel multipotent neuropeptide cocaine-and amphetamineregulated transcript (CART) has been found in a small subset of the rat's [12] and the duck's [13] PPG neurons, however the full meaning of this fi nding is still obscure.…”
Section: Introductionmentioning
confidence: 99%